Investigación de mercados diregida a servidores públicos y usuarios en general no asociados a la Cooperativa de servicios multiples de los educadores de la Regioón Huetar Norte R.L. Coopeande Nº7 R.L. - Arce-Rodríguez, Dilana (Instituto Tecnológico de Costa Rica, 2016)
This investigation is developed as Final Graduation Project to obtain the Bachelor´s degree in Business Administration. It takes into account topics like cooperativism, marketing, and descriptive investigation. It also proposes a complementary services portfolio with its own promotional plan. Due to the change that COOPEANDE N°7 R. L faced turning from a savings and credit cooperative of the North Region professors to a multiple services cooperative appears the necessity of identify new potencial services to offer. That is why this investigation intends to work as a decision making tool. This is a descriptive investigation with a qualitative approach and it was developed in Aguas Zarcas, San Carlos, taking into account the main districts of San Carlos, Los Chiles, Guatuso, and Upala for the first semester of the year 2016. The investigation concludes that there is no a unique profile of potential users of the services offer by the cooperative. Second, the most demanded services are the baby care center, health care center, mortuary services, and a stationery shop. Third, television, text messages, social network, and the email, are the most used media in the districts evaluated. Fourth, most of the people knows something about the cooperative thanks to other associates, social networks and workers from the cooperative. Fifth, there is no marketing plan to follow. Sixth, there is a high percentage of people who does not know anything about the cooperative. Finally, the frequency of use and quality of the services offer by the cooperative, as well as the reasons why people left the cooperative before, did not have significant percentages to be analyzed deeply.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2016.
Keywords: Cooperativismo; Servicios; Mercado; Mercadeo